2021
DOI: 10.1007/s11010-021-04049-w
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor and vascular response: role of soluble epoxide hydrolase, adenosine A1 receptor and angiotensin-II

Abstract: Previously, we have reported that the coronary reactive hyperemic response was reduced in adenosine A 2A receptor-null (A 2A AR −/− ) mice, and it was reversed by the soluble epoxide hydrolase (sEH) inhibitor. However, it is unknown in aortic vascular response, therefore, we hypothesized that A 2A AR-gene deletion in mice (A 2A AR −/−

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…61,62 Moreover, previous studies also showed the close association between ADORA2A and Ang in angiogenesis. 63,64 Therefore, we speculate that Ang may affect placental angiogenesis as a target gene of adenosine-ADORA2A signaling. We also found that Ang overexpression could rescue the angiogenesis inhibited by ADORA2A knockdown under adenosine treatment.…”
Section: Discussionmentioning
confidence: 95%
“…61,62 Moreover, previous studies also showed the close association between ADORA2A and Ang in angiogenesis. 63,64 Therefore, we speculate that Ang may affect placental angiogenesis as a target gene of adenosine-ADORA2A signaling. We also found that Ang overexpression could rescue the angiogenesis inhibited by ADORA2A knockdown under adenosine treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Adenosine A2A receptor (ADORA2A), which belongs to the family of adenosine receptors that are most abundant in the brain, has been reported to contribute to neuroinflammation and synaptic and neuronal damage (18) and is considered a biomarker of brain diseases. A study using adenosine A2A receptor-null (Adora2a-/-) mice demonstrated its role in the coronary reactive hyperemic response and vascular contraction (19). Another study using Adora2a-/mice showed that inactivation of endothelial ADORA2A protected mice from cerebral ischemia-induced brain injury and improved post-stroke outcomes through antiinflammatory effects and blockade of NLRP3 inflammasome activity (20).…”
Section: Discussionmentioning
confidence: 99%
“…Renin-angiotensin system (RAS) is highly affected in Covid-19 owing to the down-regulation of ACE2 and interconnected with the progress of ALI, ARDS, and injury in multiple organs [ 47 ]. It has been reported recently that DIP reduces RAS and circulating AngII serum levels through an AD-dependent pathway [ 46 , 47 ] or PDE inhibition pathway [ 48 , 49 ]. Furthermore, DIP also mitigates Covid-19-induced complications like acute kidney injury [ 50 ], acute coronary syndrome [ 51 ], acute brain injury [ 52 ], and cytokine storm-mediated multi-organ injury [ 53 , 54 ].…”
Section: Adenosinergic Pathway and Dip In Covid-19mentioning
confidence: 99%